(untitled) (Research, Society and Development, 2021)
In the search for an alternative control against Aedes aegypti, many types of research are developed to discover substitutes for synthetic insecticides, including the use of oils, extracts, or active constituents from plants to find new insecticidal substances. The present work describes the phytochemical study results and evaluation of toxicity against Aedes aegypti larvae of ethanol extracts from Azadirachta indica A. Juss collected in Tauá-CE. Phytochemical tests were performed by different methods involving colorimetric, precipitation reactions, various metabolites such as alkaloids, anthocyanidins, anthocyanins, steroids, and flavonols, flavonones, triterpenoids was evident in the active extracts. For the toxicity tests, different concentrations of ethanolic extracts (250, 500, 1000 and 2000 μg / mL) were prepared with sterile distilled water and dimethylsulfoxide - DMSO (1%), and then 20 mL of each solution was added. And 25 3rd stage larvae in plastic cups. All bioassays were performed in quadruplicate. DMSO in an aqueous solution was used as a negative control. As a result, the tested extracts proved toxic to Aedes aegypti larvae, with an LC50 value higher than the control (10%) and ranging from 12% to 46%. The results obtained show that all extracts have an important pharmacological and toxicological potential. They deserve to be investigated in studies for the isolation and identification of bioactive compounds.